Sovereign Mars : transforming our values through space settlement - Haqq-Misra, Jacob (Lawrence, Kansas : University Press of Kansas, 2023)
"Astrobiologist Jacob Haqq-Misra argues that settling Mars offers humankind a transformative opportunity to avoid the mistakes of the past by "liberating Mars" as a sovereign planet from the start. Rather than see space as a way to escape human problems on Earth, Mars presents humanity with a challenge to address these problems by thinking carefully about the theory and practice of civilization. Drawing on past examples of cooperative sovereignty, such as the Outer Space Treaty of 1967, the Federal Land Policy and Management Act of 1976, and the Antarctic Treaty System, Liberate Mars makes the case for an analogous approach to space that will preserve the space environment and benefit future generations"--
Why live in space? -- Sovereignty on Earth -- An outer space treaty -- The law of the sea -- The Antartic treaty system -- Cooperative sovereignty on Mars -- Transformative value -- Sovereign Mars -- Deep altruism -- Think like a Martian.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 15, 2023).
eBooks on EBSCOhost
Keywords: Martian bases -- International cooperation; Space colonies -- International cooperation; Human settlements -- International cooperation; Sovereignty; Treaties; Mars (Planet) -- Exploration -- International cooperation; Bases martiennes -- Coopération internationale; Colonies spatiales -- Coopération internationale; Établissements humains -- Coopération internationale; Souveraineté.; Traités.; Mars (Planète) -- Exploration -- Coopération internationale; sovereignty; treaties; SCIENCE / Space Science / Space Exploration; POLITICAL SCIENCE / Public Policy / Science & Technology Policy; Human settlements -- International cooperation; Planets -- Exploration -- International cooperation; Sovereignty; Treaties; Mars (Planet)